a) 3=a×2+b
5=a×4+b
3=2a+b /×(-1)
5=4a+b
-3=-2a-b
5=4a+b
-3+5=-2a+4a
5=4a+b
2a=2 /:2
5=4a+b
a=1
5=4+b
a=1
-b=-5+4
a=1
-b=-1 /×(-1)
a=1
b=1
równanie tej prostej to y=x+1
b)3=-2×a+b
-5=4×a+b /×(-1)
3=-2a+b
5=-4a-b
3+5=-2a+(-4a)
5=-4a-b
8=-6a /:(-6)
5=-4a-b
a=-1⅓
5=-4×(-1⅓)-b
a=-1⅓
5=5⅓-b
a=-1⅓
b=-5+5⅓
a=-1⅓
b=⅓
Równanie tej prostej to : y=-1⅓x+⅓
c)0=2×a+b
6=-2×a+b
0=2a+b
6=-2a+b
-b=2a /×(-1)
b=-2a+b
b=-2a
6=-2a+(-2a)
b=-2a
6=-4 /:(-4)
b=-2a
a=-1½
b=-2×(-1½)
a=-1½
b=3
a=-1½
Równanie tej prostej to : y=-1½x+3